2018
DOI: 10.1016/j.jjcc.2018.02.018
|View full text |Cite|
|
Sign up to set email alerts
|

Prospective observational study in elderly patients with non-valvular atrial fibrillation: Rationale and design of the All Nippon AF In the Elderly (ANAFIE) Registry

Abstract: The ANAFIE Registry will provide a valuable database for the clinical status, management, and outcomes of mortality, stroke, systemic embolism, and hemorrhagic events with/without anticoagulation in the increasing population of elderly NVAF patients, and will identify risk factors associated with these clinical events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
60
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 36 publications
(60 citation statements)
references
References 46 publications
0
60
0
Order By: Relevance
“…Invasive procedures (except those related to AF) and other clinical events were also recorded. 32 Registry UMIN000024006) is a multicenter, prospective, observational (non-interventional) registry of elderly NVAF patients (aged ≥75 years) from across Japan; full details of the registry have been reported previously. 32, 33 Patient enrollment in the registry started in October 2016 (target, 30,000 patients), and follow-up data were collected at month 12 and month 24.…”
Section: Data Collectionmentioning
confidence: 99%
“…Invasive procedures (except those related to AF) and other clinical events were also recorded. 32 Registry UMIN000024006) is a multicenter, prospective, observational (non-interventional) registry of elderly NVAF patients (aged ≥75 years) from across Japan; full details of the registry have been reported previously. 32, 33 Patient enrollment in the registry started in October 2016 (target, 30,000 patients), and follow-up data were collected at month 12 and month 24.…”
Section: Data Collectionmentioning
confidence: 99%
“…The 2-year follow-up observation and planned subcohort studies, 16 including data on biomarkers, ECG, heart rate, hypertension, cognitive function, frailty, and treatment adherence, will further illuminate real-world clinical practices for the treatment of NVAF in the era of DOAC therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The study design and ethical considerations have been reported previously. 16 Briefly, patients eligible for the study included those aged ≥75 years with a definitive diagnosis of NVAF based on ECG. Patients who were currently partici-Registry in Atrial Fibrillation) study demonstrated that the absolute benefit of oral anticoagulants was higher in patients with AF aged ≥85 years than in those aged <85 years.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We note, however, that patient selection and regional enrollment biases are limitations of all prospective observational studies. The largest prospective observational study in elderly patients with non-valvular atrial fibrillation will provide important insights into understanding the clinical outcomes among Japanese AF patients [22]. Nevertheless, as noted in other registry-based studies in Japan, similarity exists within patient groups, depending on the type of facility at which they are being treated.…”
Section: Limitationsmentioning
confidence: 98%